Beginnings of Arabic Grammar between pre-Islamic and Early Islamic Times: ARABIC GRAMMAR HISTORY - Anwer Rakan Shallal (Al-Ḍād Journal, 2022)
The aim of this research is to reveal the existence of Arabic grammar in the pre-Islamic era and the era of Islam, contrary to what some researchers argue that Arabic grammar appeared at the end of the second century AH, and we mentioned in this research examples of the phenomenon of expression in ignorance and the issue of Islam, and the emergence of terms (Arabic, grammar, melody, power) in an advanced era, and this means the existence of rules and compositions of this science at that time. This fact can be shown by the Arabs’ knowledge of the Qur’an, which began to descend at the beginning of Islam, they understood his words and verses and did not object to a mistake and a mistake in it. If it had been different, he would have attacked those who rejected the Islamic call, as well as we can say that the Arabs knew the grammatical rules and composition naturally without the need to learn them, and the learning of Arabic becomes active with writing grammar and writing in Arabic at a later stage when the non-Arabs began to enter Islam and because of they have no knowledge about the language that they start studying Arabic to learn the new religion, Quran and Islam. Keywords: Before Islam, Arabic, Grammar, Islam, Melody